People with Speech Differences as Ethnographers: Implications for Research - Bennett, Andrew B. (Disability Studies Quarterly, 2013)
Individuals with speech disabilities who perform ethnographic researcher can exhibit certain vulnerabilities. Vulnerabilities are generally tied to participants (Behar, 1996). These vulnerabilities generally focus on some particular attribute (Duffy, 2008). However, Ballamingle and Johnson (2011) argue that researchers can also be vulnerable. Broun and Heshusius (2004) had previously demonstrated how physical vulnerabilities can impact researchers with disabilities. Researcher vulnerabilities, as well as potential strengths, are important because of the role of speech in the ethnographic research practice. This article shall describe issues involved with the actual doing of ethnographic research. This discussion focuses on speech while doing fieldwork. In addition, to the discussion of fieldwork, this article also discusses the presentation of the work, especially with regards to professional conferences. Keywords: ethnographic practice, speech disability, role of researchers, researcher vulnerability, presentations